COMPARATIVE ANALYSIS OF TAX EVASION BETWEEN MOLDOVA AND ROMANIA - OANA-CARMEN RĂVAŞ (Annals of the University of Petrosani: Economics)
Tax evasion is actually failure by the taxpayer, tax liabilities. And the negative effects of this are felt directly on the level of tax revenue receipts, causing major distortions in the functioning of the market mechanism. It is believed that the first cause of fraud is itself impossible, fairer tax system in which develops based on the principle of declaring taxpayer benefiting from a presumption of honesty and that is a temptation to hide.